EFFICIENCY OF DYNAMIC ELECTRONEUROSTIMULATION IN SPORTSMEN WITH SUPPORTING-MOTOR APPARATUS INJURIES - V. Yu. Zhukova; V. V. Gordeev; Yu. F. Lobanov (Вопросы современной педиатрии, 2014)
Aim: The purpose of the study is to evaluate the clinical efficiency of electrodynamic rehabilitation methods in teenager sportsmen withsupporting-motor apparatus (SMA) injuries. Patients and methods: 46 boys in the age of 14–16 with SMA injuries participated in the study. 20 boys received only conventional rehabilitation remedies (physiotherapy, remedial gymnastics, massage and taping), while the treatment of other 26 boys was enhanced with the DENS therapy. Duration of procedures was 30–40 minutes, duration of the whole treatment course — 10–14 days. The clinical effect of the DENS therapy was evaluated according the progress of clinical symptoms and life quality indices assessment result (before and immediately after and one month after the rehabilitation course), sing the evidentiary medicine methods. Results: After the two-week course of the DENS therapy the absolute risk reduction (ARR) in the teenagers withSMA injuries was fluctuating between 34.6 (8.7–60.5)% (physical performance) and 56.9% (33.1–80.8%; school performance; р = 0.022), while the relative risk reduction (RRR) by the same indicators was equal to 69.2% (16.2–88.7%) and 71.1% (39.8–86,2%; р = 0.002). The relative risk (RR) was registered at the level of 0.31 (0.11–0.89; р = 0.022) and 0.29 (0.14–0.86; р = 0.0002). The ARR value higher than 50% always indicates the clinically significant effect while the ARR value between 25 and 50% indicates the clinically significant effect very often. The following indicators according to the MDASI questionnaire were significantly improved within the test group: pain (p = 0.001), sleet disturbance (p = 0.050) and feeling of depression (p = 0.045). According to the PedsQL™4.0 questionnaire data, the significant improvement of the emotional performance (from 83.7 ± 6.97 to 91.2 ± 3.75) was registered in the point II. Conclusion: The rehabilitation course showed significant clinical effect in young sportsmen with SMA injuries. Introduction of the DENS therapysignificantly reduces the frequency of adverse outcomes and improves the clinical effect of rehabilitation.